Peritoneal dialysis for the treatment of cardiorenal syndrome type 1: A prospective Brazilian study - Ponce, Daniela [UNESP]; Góes, Cassiana [UNESP]; Oliveira, Mariele [UNESP]; Balbi, Andre [UNESP] (SAGE Publications, 2017)
This study aimed to explore the role of high-volume peritoneal dialysis (HVPD) in cardiorenal syndrome (CRS) type 1 patients in relation to metabolic and fluid control and outcome. Sixty-four patients were treated by HVPD (prescribed Kt/V = 0.50/session), flexible catheter and cycler. Mean age was 68.8 ± 15.4 years, 54.7% needed intravenous inotropic agents and/or intravenous vasodilators, 31.2% were on mechanical ventilation, acute coronary syndrome (ACS) was the main cause of acute disease heart failure (ADHF) 48.3%, median left ventricular ejection fraction (LVEF) was 38% and the main dialysis indications were uremia and hypervolemia. Blood ureic nitrogen and creatinine levels stabilized after 4 sessions at around 50 and 4 mg/dL, respectively. Negative fluid balance (FB) and ultrafiltration (UF) increased progressively and stabilized around 2.6 L and -2.5 L/day, respectively. Weekly-delivered Kt/V was 3.0 ± 0.42, and 32.8% died. There was a significant difference between the survivors (S) and non-survivors (NS) in age (71.4 ± 15.7 vs 63.6 ± 17.6, p < 0.001), main diagnosis of ADHF (ACS: 76.2 vs 34.8%, p = 0.04), mechanical ventilation (52.4 vs 20.1%, p = 0.03), fluid overload (FO) at predialysis moment (52.4 vs 25.6%, p = 0.04), and FB and UF from the 2nd to 5th dialysis session. In conclusion, HVPD treatment was effective in CRS type 1 patients, allowing adequate metabolic and fluid control. Age, ACS, FO and positive FB after 2 HVPD sessions were higher in NS patients.
Keywords: Acute kidney injury; Cardiorenal syndrome; Peritoneal dialysis